2022
DOI: 10.3390/su142114063
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Cyberbullying Victimization and Associated Factors among Adolescents in Six European Countries

Abstract: Bullying and cyberbullying victimization are significant factors that threaten adolescent development and mental health. Our study aimed to analyze how socioeconomic characteristics and personal experiences of violence are associated with adolescents’ experiences of bullying and cyberbullying victimization. The study participants were 1146 students, 698 females and 448 males, aged between 13 and 16 years old, from secondary schools in Spain, Italy, Romania, Portugal, Poland and the UK. Data was collected throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Participants who assumed the victim role displayed psychopathological behaviors such as depressive symptomatology, loneliness leading to energy loss, paranoia accompanied by neurosis and fear, psychopathic deviance causing inhibition, schizophrenia leading to low interpersonal relationships and neurosis, and psychasthenia, characterized by anxiety and neuroticism [21][22][23][24]. These results are in line with previous research that shows that the role of the victim in cyberbullying shows personality traits or psychopathological behaviors characterized by depression, anxiety, low interpersonal skills, loneliness, etc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants who assumed the victim role displayed psychopathological behaviors such as depressive symptomatology, loneliness leading to energy loss, paranoia accompanied by neurosis and fear, psychopathic deviance causing inhibition, schizophrenia leading to low interpersonal relationships and neurosis, and psychasthenia, characterized by anxiety and neuroticism [21][22][23][24]. These results are in line with previous research that shows that the role of the victim in cyberbullying shows personality traits or psychopathological behaviors characterized by depression, anxiety, low interpersonal skills, loneliness, etc.…”
Section: Discussionsupporting
confidence: 89%
“…As interpersonal interactions occur, openness can become a persistent form of harassment [17,20]. Victims often exhibit depressive symptoms, low emotional intelligence, fear, social isolation, shyness, and introversion [21][22][23][24][25]. Aggressors typically display antisocial and criminal behaviors, a lack of empathy, extraversion, a lack of self-control, and cruelty [7,23,26].…”
mentioning
confidence: 99%
“…These results may be associated with youth who experience school violence situations having lower ability to cope with stress [ 20 ], which is related to a higher consumption of harmful substances and a lower self-esteem [ 19 , 22 ]. However, higher self-esteem is related to a lower probability of being a victim of school violence [ 29 ]. Studies address that youth exposed to violence have risk behaviors, such as substance abuse and worse life satisfaction [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high self-esteem may be associated with a higher likelihood of engaging in healthy behaviors, such as good nutrition and regular exercise [ 28 ]. In relation to school violence, it is observed that individuals with higher self-esteem present a lower susceptibility to being victims of bullying and/or cyberbullying [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it has been observed that, overall, being male, younger in age, having a below-average socioeconomic status, and receiving low peer and parental support were associated with a greater risk of bullying victimization [15]. Some authors have demonstrated that prevalence rates of bullying victimization in Europe are lower compared with those observed in Africa and America, although more recent evidence showed an overall noteworthy prevalence of 36.39% in European countries [17]. In the Italian school context, 20% of students between 11 and 17 years reported having been bullied two or more times in a month [18].…”
Section: Introductionmentioning
confidence: 99%